Very Low-Carbohydrate High-Fat Diet Improves Risk Markers for Cardiometabolic Health More Than Exercise in Men and Women With Overfat Constitution: Secondary Analysis of a Randomized Controlled Clinical Trial - Cipryan, Lukas; Litschmannova, Martina; Maffetone, Philip B.; Plews, Daniel J.; Dostal, Tomas; Hofmann, Peter; Laursen, Paul B. (Frontiers in Nutrition, 2022)
Purpose: This randomized controlled parallel-group study examined the effects of a very low-carbohydrate high-fat (VLCHF) diet and high-intensity interval training (HIIT) program over 12-weeks on cardiometabolic risk factors in overfat individuals with overfat constitution. Methods: Ninety-one participants out of 109 completed the study. The participants were randomly allocated to the HIIT (N=22), VLCHF (N=25), VLCHF+HIIT (N=25), or control (N=19) groups for 12 weeks. Fasting plasma samples were collected before the intervention and after 4 and 12 weeks. The analyzed outcomes included complete blood count, glucose, insulin, glycated hemoglobin, triglycerides (TG), cholesterol, high- and low-density lipoprotein (HDL-C and LDL-C), lipoprotein(a), adiponectin (Adpn), leptin (Lep), tumor necrosis factor α (TNF-α), and other interleukins (hs-IL-6, IL-1RA, IL-1β, and IL-10), and IL-1RA. The homeostasis model assessment of insulin resistance (HOMA-IR), Adpn/Lep ratio, TG/HDL-C ratio, and TyG index were calculated and analyzed. Blood pressure was measured before the intervention, after 4, 8, and 12 weeks (ClinicalTrials.gov: NCT03934476). Results: Absolute changes in HOMA-IR, Adpn/Lep ratio, LDL-C, and diastolic blood pressure after 12 weeks differed by study groups (p < 0.05). The most pronounced changes were revealed in the VLCHF (∆M [95% CI]; HOMA-IR: -0.75 [-1.13; -0.55]; Adpn/Lep: 9.34 [6.33; 37.39]; LDL-C: 0.06 [-0.12; 0.50] mmol/l) and VLCHF+HIIT (HOMA-IR: -0.44 [-1.14; 0.12]; Adpn/Lep: 4.26 [2.24; 13.16]; LDL-C: 0.25 [-0.04; 0.50] mmol/l) groups. The triglyceride-glucose (TyG) index and TG/HDL-C ratio significantly decreased in the VLCHF (-0.74 [-2.11; -0.27] and -0.13 [-0.40; -0.04], respectively) and VLCHF+HIIT (-0.68 [-1.89; 0.00] and -0.18 [-0.65; -0.03]) group. Conclusions: A 12-week VLCHF diet intervention in overfat individuals with overfat constitution is effective for favorable changes in HOMA-IR (compared to HIIT), Adpn/Lep ratio, TyG index, TG/HDL-C ratio, and diastolic blood pressure. HIIT, or HIIT combined with the VLCHF diet, had no additional benefits for the analyzed variables. No adverse side effects were observed.